2019
DOI: 10.1002/hed.25712
|View full text |Cite
|
Sign up to set email alerts
|

Thyroidectomy in octogenarians is not associated with poorer postoperative outcomes

Abstract: Background The elderly represents one of the most rapidly growing subsets of the population. This population experiences a higher incidence of thyroid pathology. However, there are concerns that the elderly also experiences increased perioperative complications and are poor candidates for thyroidectomy. Methods Patients who underwent thyroidectomy over the age of 80 years at three tertiary head and neck units were included. Data regarding age, sex, presenting symptoms, comorbidities, preoperative investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…36,37 Previous studies in patients undergoing head and neck surgery support our conclusion and encourage the use of preoperative predictive models for postoperative serious complications in octogenarians. [38][39][40][41] The limitations of this study are its retrospective nature and sample size. Due to the relatively small number of complications recorded, we were limited in our ability to assess risk factors associated distinctly with each complication type.…”
Section: Discussionmentioning
confidence: 98%
“…36,37 Previous studies in patients undergoing head and neck surgery support our conclusion and encourage the use of preoperative predictive models for postoperative serious complications in octogenarians. [38][39][40][41] The limitations of this study are its retrospective nature and sample size. Due to the relatively small number of complications recorded, we were limited in our ability to assess risk factors associated distinctly with each complication type.…”
Section: Discussionmentioning
confidence: 98%
“…Compared with other types of surgeries, e.g., benign surgery [25,26] and malignant surgery [27] in patients aged 80 years or older, thyroid surgery is considered safe [28]. However, the state of health and the preoperative comorbidities of these patients play a crucial role in the postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The data regarding the safety of total thyroidectomy in older‐adults are conflicting. Institutional series show that total thyroidectomy is safe in older‐adult (age >65) and oldest‐old (age >80) patients, with relatively low complication rates [7, 8]. Other institutional series demonstrate a significantly higher overall complication rate in oldest‐old patients (24% vs. 9%, p < 0.001) [13].…”
Section: Discussionmentioning
confidence: 99%
“…The data regarding morbidity after thyroidectomy in older‐adults (age ≥65) are conflicting. Institutional series suggest that it is a well‐tolerated procedure with minimal morbidity [7, 8]. However, several analyses of the American College of Surgeons National Surgical Quality Improvement Program (ACS‐NSQIP) database have suggested that thyroidectomy in older‐adults is associated with increased risk for postoperative morbidity [9, 10].…”
Section: Introductionmentioning
confidence: 99%